Territorial Tax System Reform and Corporate Financial Policies - Arena, Matteo P.; Kutner, George W. (Review of Financial Studies, 2015)
We examine the effect of a permanent change to a country corporate income repatriation tax system on corporate financial policies. In 2009, Japan and the United Kingdom switched from a worldwide system to a territorial system for the taxation of repatriated foreign earnings, effectively reducing the tax liabilities of most multinational firms when repatriating earnings. We find that after the change firms accumulate less cash, pay out larger amounts through dividends and share repurchases, and invest less abroad. We do not find that the tax system change has significantly affected domestic investments even when controlling for capital constraints.